2007
DOI: 10.1007/s11104-007-9231-7
|View full text |Cite
|
Sign up to set email alerts
|

Micro-PIXE studies of elemental distribution in sap-feeding insects associated with Ni hyperaccumulator, Berkheya coddii

Abstract: The aim of this study was to determine elemental composition of sap-feeding insects inhabiting various parts of the Ni hyperaccumulating plant Berkheya coddii Roessl., the endemic species of ultramafic outcrops in Mpumalanga, South Africa. Three species were examined: the aphid Protaphis pseudocardui (Aphididae), abundant on young leaves; the mealybug Orthesia sp. (Ortheziidae) colonizing underground parts of this plant, and the bug Norialsus berkheyae (Cixiidae) living on young shoots. Maps of Ni, K, Ca, Zn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…The digestive system of myriapods and other terrestrial arthropods, especially the midgut epithelium, is a first line of defense against toxic substances, playing a role in the elimination of pathogens and harmful materials that originate in food (Hopkin ; Loeb & Hakim ; Migula et al. ; Rost‐Roszkowska et al. ; Hakim et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The digestive system of myriapods and other terrestrial arthropods, especially the midgut epithelium, is a first line of defense against toxic substances, playing a role in the elimination of pathogens and harmful materials that originate in food (Hopkin ; Loeb & Hakim ; Migula et al. ; Rost‐Roszkowska et al. ; Hakim et al.…”
mentioning
confidence: 99%
“…The digestive system of myriapods and other terrestrial arthropods, especially the midgut epithelium, is a first line of defense against toxic substances, playing a role in the elimination of pathogens and harmful materials that originate in food (Hopkin 1989;Loeb & Hakim 1996;Migula et al 2007;Rost-Roszkowska et al 2008;Hakim et al 2010). In myriapods, toxic metals are accumulated in the midgut epithelial cells, where they are neutralized in crystalline structures called spherites.…”
mentioning
confidence: 99%
“…For example, Migula et al (2007) suggested that how collected specimens are handled after capture could affect whole-body Ni measurements. Insects killed immediately upon capture would retain their gut contents, whereas those captured but not immediately killed would have the opportunity to at least partially empty their digestive tracts.…”
Section: Where Is Ni In Insect Bodies?mentioning
confidence: 99%
“…Note that, as mentioned previously, an insect species may meet the criterion described above for samples of larvae or nymphs but not for samples of adults (or vice versa), from the same insect species. This is illustrated by Anoplocnemis dallasiana Lethierry & Serville (Heteroptera: Coreidae) in Table 1: Migula et al (2007) reported 1 300 +g Ni/g in nymphs but only 280 +g Ni/g in adults. In the reverse situation, they reported less from nymphs (43 +g Ni/g) but more from adults (520 +g Ni/g) of Rhinocoris neavei Bergroth (Heteroptera: Reduviidae).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation